1991
DOI: 10.1002/bio.1170060303
|View full text |Cite
|
Sign up to set email alerts
|

The effect of buffers and chelators on the reaction of luminol with Fenton's reagent near neutral pH

Abstract: The chemiluminescence of the system luminol +Fe2+ +H2O2 was measured in aqueous buffer at pH 7.2. In veronal (5,5-diethybarbiturate) buffer, the luminescence is strongly quenched by ethanol and mannitol, but only weakly by t-butanol, benzoate and superoxide dismutase (SOD); complexing Fe2+ with 1,20-phenanthroline or 2,2'-dipyridyl causes a decrease of light production that can be partially obviated by the simultaneous addition of SOD. In phosphate buffer, the luminescence is higher than in veronal and it is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The following 0.1 mol/L buffers were used at different pHs: sodium acetate (pH 4.0, 4.5, 5.0 and 5.5); sodium citrate (pH 6.0, 6.25, 6.5 and 6.75); potassium phosphate (pH 7.0, 7.25, 7.5, 7.75 and 8.0); sodium borate (pH 8.25, 8.5, 9.0 and 9.5); and sodium carbonate (pH 10.0 and 10.5). Initially sodium diethyl barbiturate was used at pH 8.0 and 8.5, but we found that this buffer had scavenger abilities, confirming the findings of Bottu (9,10).…”
Section: Methodssupporting
confidence: 80%
“…The following 0.1 mol/L buffers were used at different pHs: sodium acetate (pH 4.0, 4.5, 5.0 and 5.5); sodium citrate (pH 6.0, 6.25, 6.5 and 6.75); potassium phosphate (pH 7.0, 7.25, 7.5, 7.75 and 8.0); sodium borate (pH 8.25, 8.5, 9.0 and 9.5); and sodium carbonate (pH 10.0 and 10.5). Initially sodium diethyl barbiturate was used at pH 8.0 and 8.5, but we found that this buffer had scavenger abilities, confirming the findings of Bottu (9,10).…”
Section: Methodssupporting
confidence: 80%
“…Aqueous solutions of divalent transition metal cations such as Cu 2+ , Fe 2+ , Co 2+ , and Mn 2+ are well known to catalyze the chemiluminescence of luminol in the presence of dissolved O 2 and/or H 2 O 2 . In the presence of H 2 O 2 , significant increases in emitted light intensity may be produced by even trace concentrations of transition metal cations . The exact mechanism of this transition metal catalysis is not known but the production of HO • through a Fenton type reaction has been suggest as an important step, i.e., It is also known that the complexation of divalent transition metal cations by chelating agents such as EDTA greatly diminishes their ability to catalyze luminol chemiluminescence. , On the basis of the above it is first proposed that the levels of background light emission observed in the absence of added EDTA result from luminol chemiluminescence catalyzed by traces of transition metal cation present in the reagents and/or water used in our experiments. Metal cations leaching from apparatus and glassware could also contribute.…”
Section: Resultsmentioning
confidence: 99%
“…The study of luminol SCL in the presence of H 2 O 2 is potentially complicated by a background (nonsonochemical) process of chemiluminescence catalyzed by trace concentrations of divalent transition metal cations. Transition metal contamination of solutions through impurities present in reagents or through leaching from equipment is difficult to avoid completely. However, chelating agents such as EDTA are known to complex the cations involved, greatly reducing their catalytic activity. , Here we show how EDTA may be used to suppress the background chemiluminescence of aqueous solutions containing luminol and H 2 O 2 while minimally affecting SCL, thus simplifying the acquisition of SCL intensity data.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the first step in this study was to ensure that the experimental conditions were optimal and that they did not generate artifacts. Ethanol acts as an • OH scavenger under some experimental conditions [26]. We investigated the effect of ethanol in reducing DNA damage induced by Cr(III) plus H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%